Morphological characterization and assessment of genetic variability in Hibiscus rosa-sinensis: A Comparative Study - SHAKES, ANCHU ANNA; BASHEER, SHAJMA NAFEESA; SANKAR, MINI; KUMAR G., KRISHNA; K., SHAHIDA (Journal of Ornamental Horticulture, 2025)
The present study was conducted to evaluate the quantitative and qualitative traits of twenty Hibiscus rosa-sinensis genotypes. Wide variation was observed among the genotypes for almost all the leaf and flower morphological characters. Ovate, cordate and circular leaf shapes were found among the genotypes with serrate or crenate type of incision. The leaf colour varied between three shades of green. The genotype CO 2 recorded the maximum leaf length (12.8 cm) and leaf width (8.3 cm), while the minimum leaf length and leaf width were observed in the genotypes KAU Hb 43 and KAU Hb 42 respectively. Among the flower characters, KAU Hb 38 produced the largest flowers with the highest flower diameter (15.77 cm) while genotypes KAU Hb 42 and KAU Hb 13 produced smaller flowers with least diameter of 6.80 cm and 6.9 cm respectively. The genotype with the longest petal was KAU Hb 38 (8.63 cm) and the broadest petal was seen in KAU Hb 43 (6.03 cm). The maximum fresh weight of flowers was 4.97g for the genotype KAU Hb 3. A wide range of colours were also observed in the flowers and leaves of hibiscus genotypes. Cluster analysis was done to group the genotypes into four clusters based on the diversity in morphological characters and variability analysis was done to ensure effective selection of genotypes for further breeding programmes.